Homogenous scales of narcissism: Using the psychological entitlement scale, interpersonal exploitativeness scale, and narcissistic grandiosity scale to study narcissism. (1st March 2018) - Brunell, Amy B.; Buelow, Melissa T.
Abstract: We examined the extent to which the Psychological Entitlement Scale (PES), the Interpersonal Exploitativeness Scale (IES), and the Narcissistic Grandiosity Scale (NGS), when taken together, assess a broader construct or three distinct facets. In Study 1, a principal components analysis was conducted, demonstrating that the PES, IES, and NGS should be considered three separate traits rather than one overall construct. In Study 2, confirmatory factor analysis (CFA) revealed that the most efficient and best fitting model contained 8 items of the PES (dropping a reverse-scored item), the 6-item IES, and a revised 6-item model of the NGS. Study 3 replicated the CFA and examined the correlates of the PES, IES, and NGS with measures of narcissism and related measures such as empathic concern and self-esteem. Implications for future assessment of narcissism traits are discussed. Highlights: Assesses entitlement, exploitativeness, and grandiosity as facets of narcissism. Study 1 used principal components analysis to assess these facets. Study 2 used confirmatory factor analysis to assess model fit. Study 3 examined the correlates of entitlement, exploitativeness, and grandiosity.